1995
DOI: 10.1128/mcb.15.10.5576
|View full text |Cite
|
Sign up to set email alerts
|

9-cis Retinoic Acid Inhibition of Activation-Induced Apoptosis Is Mediated via Regulation of Fas Ligand and Requires Retinoic Acid Receptor and Retinoid X Receptor Activation

Abstract: T-cell hybridomas, thymocytes, and T cells can be induced to undergo apoptotic cell death by activation through the T-cell receptor. This process requires macromolecular synthesis and thus gene expression, and it has been shown to be influenced by factors regulating transcription. Recently, activation, T-cell hybridomas rapidly express the Fas/CD95 receptor and its ligand, Fas ligand (FasL), which interact to transduce the death signal in the activated cell. Retinoids, the active metabolites of vitamin A, modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 59 publications
11
74
1
Order By: Relevance
“…9). All-trans-RA is known to mediate its response through RAR (24), and TTNPB, a synthetic retinoid analog, acts as a selective RAR agonist (25). Both the all-trans-RA-and TTNPB-mediated increases in SCD mRNA expression were effectively blocked by AGN194301, a RAR␣-specific antagonist (26).…”
Section: Identification Of Scd As a Differentially Expressed Gene In mentioning
confidence: 94%
See 1 more Smart Citation
“…9). All-trans-RA is known to mediate its response through RAR (24), and TTNPB, a synthetic retinoid analog, acts as a selective RAR agonist (25). Both the all-trans-RA-and TTNPB-mediated increases in SCD mRNA expression were effectively blocked by AGN194301, a RAR␣-specific antagonist (26).…”
Section: Identification Of Scd As a Differentially Expressed Gene In mentioning
confidence: 94%
“…TTNPB is a synthetic, highly selective RAR agonist with no affinity for RXR (25). TTNPB induced SCD expression, and the induction was blocked completely by AGN194301, an RAR␣ antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nucleus plays a central role in PCD, cellular membranes are the primary site of action of several PCD inducers and lipid messengers act as regulators of apoptosis (Bissonnette et al, 1995;McGahon et al, 1995). 5-Lipoxygenase (EC 1.13.11.34) plays a critical role in lipidmediated signal transduction (Los et al, 1995) and its metabolites were recently found to be active in the nucleus of human cells (Jakobsson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…First, retinoids are known to regulate apoptosis in T lymphocytes, thymocytes, and T lymphoma cells (7,21,44). Second, in addition to promoting Th2 development, treatment with the RXR agonist AGN194204 during primary antigenic stimulation reproducibly caused a greater accumulation of viable cells after 1 wk of culture than did treatment with the vehicle control.…”
Section: Dna Microarray Analysis Following Primary Stimulation Of Naimentioning
confidence: 99%